2020
DOI: 10.1097/pgp.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Mismatch Repair-deficient Endometrial Carcinoma and Tumor-associated Immune Cells: Differences Between MLH1 Methylated and Nonmethylated Subgroups

Abstract: Mismatch repair (MMR)-deficient endometrial carcinomas show increased programmed cell death-ligand 1 (PD-L1) expression compared with MMR-intact endometrial carcinomas, but there are limited data regarding PD-L1 expression between sporadic and inherited carcinomas exhibiting MMR loss. Most of the studies investigating PD-L1 expression in endometrial carcinoma have used tissue microarrays and did not examine all tumor blocks. In this study, we analyzed the expression of PD-L1 in resection specimens of 176 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The reason for this may be due to the homology of MLH1 and PMS2, which can form functionally paired dimers and cause degradation of the corresponding paired dimers when one of them is mutated, similar to MSH2 and MSH6 [21,22] . Further analysis in this study also revealed that PMS2 expression de ciency was also associated with PD-L1 expression (P < 0.05), and Kir et al found that PMS2 de ciency was an independent risk factor for PD-L1 positivity by analyzing 176 resected endometrial cancer specimens [23] similarly, Morgan et al found that PD-L1 was more often seen in dMMR status tumors by analyzing cervical neuroendocrine carcinomas [24] . However, studies related to the relationship between PMS2 and PD-L1 in CRC tumors are rare, and the speci c mechanism of this nding in this paper still needs to be investigated at a deeper level to be discovered, but to a certain extent, it provides research ideas for subsequent researchers.…”
Section: Discussionsupporting
confidence: 64%
“…The reason for this may be due to the homology of MLH1 and PMS2, which can form functionally paired dimers and cause degradation of the corresponding paired dimers when one of them is mutated, similar to MSH2 and MSH6 [21,22] . Further analysis in this study also revealed that PMS2 expression de ciency was also associated with PD-L1 expression (P < 0.05), and Kir et al found that PMS2 de ciency was an independent risk factor for PD-L1 positivity by analyzing 176 resected endometrial cancer specimens [23] similarly, Morgan et al found that PD-L1 was more often seen in dMMR status tumors by analyzing cervical neuroendocrine carcinomas [24] . However, studies related to the relationship between PMS2 and PD-L1 in CRC tumors are rare, and the speci c mechanism of this nding in this paper still needs to be investigated at a deeper level to be discovered, but to a certain extent, it provides research ideas for subsequent researchers.…”
Section: Discussionsupporting
confidence: 64%
“…While no association between PD-L1 mRNA expression and OS was found, mRNA expression was significantly correlated with worse progression-free survival (PFS) [27]. In a study in 2021, decreased DFS was observed in endometrial carcinoma cases with immune cell PD-L1 positivity ≥ 5% [28]. In another study, the relationship between PD-L1 expression and prognosis was studied among 120 OCCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In addition, Kiret al discovered that PMS2 deficiency was an independent risk factor for PD-L1 positivity through analysis of 176 resected endometrial cancer specimens. 29 Further analysis in our study revealed that PMS2 expression deficiency did associate with PD-L1 expression, which was consistent with the above findings (P < 0.05), the reason for this may be due to the situation that, in this study, PMS2 deficiency was the most common type of dMMR (10 in 15), and the larger amount of data makes the association between PMS2 deficiency and PD-L1 positive expression easier to detect compared to the other three proteins. However, studies related to the relationship between PMS2 and PD-L1 in CRC tumors are few, thus more in-depth studies are needed to clarify the mechanisms.…”
Section: Discussionmentioning
confidence: 99%